2022
DOI: 10.1186/s13690-022-00925-z
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequality in public satisfaction with the healthcare system in China: a quantile regression analysis

Abstract: Background As China pursues better social equality and improvement in public services (healthcare), public satisfaction has been considered as a key performance indicator. There is a great need to better understand the disparities and inequalities in the public satisfaction with its healthcare system. Methods Based on Chinese General Social Survey (CGSS) 2015 ( a set of nationally representative survey data, the most recent wave containing informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The complexity lies in the social context that China has very high individual savings rates, and the Chinese elderly tend to accumulate savings throughout their whole life cycle to deal with the reduced income and increasing medical expenditures in their later life [ 38 ]. Some existing studies that adopted objective measures such as healthcare expenditure/disposable income per capita to measure the economic burden of healthcare also found that it was not the major driving factor for healthcare satisfaction [ 39 ]. We argue that it is possible because the precautionary savings of a family reduce medical expenses and alleviate the dissatisfaction with affordability.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity lies in the social context that China has very high individual savings rates, and the Chinese elderly tend to accumulate savings throughout their whole life cycle to deal with the reduced income and increasing medical expenditures in their later life [ 38 ]. Some existing studies that adopted objective measures such as healthcare expenditure/disposable income per capita to measure the economic burden of healthcare also found that it was not the major driving factor for healthcare satisfaction [ 39 ]. We argue that it is possible because the precautionary savings of a family reduce medical expenses and alleviate the dissatisfaction with affordability.…”
Section: Discussionmentioning
confidence: 99%
“…The situation correlates with patient comfort and satisfaction [ 5 ]. Patient satisfaction is the most crucial and is one of the main reasons patients visit primary healthcare [ 6 ]. Experience in Canada, several factors influence the use of primary healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…Amoah et al. [ 22 ] found that employed persons show a higher likelihood of being satisfied with the health system, while Peng and Zhang [ 24 ] reported the opposite result.…”
Section: Introductionmentioning
confidence: 99%